2019
DOI: 10.1002/csr.1859
|View full text |Cite
|
Sign up to set email alerts
|

The (in)congruence of measures of corporate social responsibility performance and stakeholder measures of corporate social responsibility reputation

Abstract: A central proposition of the “business case” for corporate social responsibility (CSR) is that a company's CSR practices are linked to consumer behavior and a firm's financial performance through reputational mechanisms. This study addresses the equivocal support for this proposition through an empirical analysis of the survey items most often used to assess a company's CSR and its stakeholder reputation. This study tests the congruence among nine different measures of environmental, social, and governance dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 92 publications
2
33
0
Order By: Relevance
“…This study is complementary to previous studies [28,44,57,71,[86][87][88] that have shown the role that corporate governance has in the frame of this process and, implicitly, in the drafting of the accounting synthesis accounts, as well as the role that these have in the governing of an entity.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This study is complementary to previous studies [28,44,57,71,[86][87][88] that have shown the role that corporate governance has in the frame of this process and, implicitly, in the drafting of the accounting synthesis accounts, as well as the role that these have in the governing of an entity.…”
Section: Discussionmentioning
confidence: 46%
“…Another correlation identified by the specialists is related to the degree of responsibility, the expertise of the members of the audit committee, and the financial performance. In fulfilling its supervisory, internal control, and financial reporting responsibilities, the audit committee should have the necessary expertise based on accounting and financial forecasting [55][56][57], accounting, control, and auditing [58] to ensure the superior quality of financial reporting [59]. Tenure, the regularity of the consultations, and social ties can also have an impact of great significance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The empirical findings' mixed results have been linked to measurement problems; solving the measurement problem would provide a clearer relationship (Yang & Stohl, 2020). Given the confounding results from the existing empirical studies and the fact that many of them did not investigate CSR on Community Development, Health, and Education, coupled with various limitations in their methodologies, this study shall test the following hypotheses: H01: CSR on Community Development does not significantly affect the financial performance of Deposit Money Banks in Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…From time to time, numerous governmental and non-governmental organisations worldwide are involved in many CSR initiatives costing billions of dollars (Sulphey, 2017). The conceptual support for CSR is that CSR practices would enhance firms' reputations in the consumers' sight and thereby lead to improved performance (Yang & Stohl, 2020). One school of thought is that CSR could be adopted as a firm strategy to develop a competitive advantage over the competitors, which would increase profitability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that the two hypotheses intersect (Korppi, Mecklin, & Heikkilä, 2019). Nonetheless, a crucial literature search shows that the examination of CSR and Stakeholder Management work has primarily concerned with their connection with business performance (Yang & Stohl, 2020). By demonstrating responsiveness and accountability to stakeholders with regard to CSR issues, one would hope that the corporate reputation would flourish and the organization's market performance would benefit.…”
Section: Introductionmentioning
confidence: 99%